FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH KABUPATEN BADUNG TAHUN 2006-2021 - Monika Pratiwi, Ni Putu; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
On the island of Bali, Badung Regency is the district with the highest PAD contribution, which is reliant on the tourism industry. However, the COVID-19 pandemic that struck in 2020–2021 caused a decline in Badung Regency's economy, necessitating the development of fresh strategies to stimulate the sector. Therefore, the purpose of this study is to identify the variables that will affect PAD Badung Regency between 2006 and 2021. Secondary data in the form of time series data is the type of data used in this study. Multiple linear analysis is the method of data analysis employed. According to the study's findings, PAD Badung Regency is partially impacted by the number of tourists and the population in the productive age group. The PAD of the Badung Regency, however, is not significantly impacted by hotel occupancy rates or BPHTB. The research has implications for the government's ability to continue maintaining quality and managing the tourism sector in Badung Regency optimally so that domestic tourists continue to visit the region. This research is consistent with the PAD theory that local taxes and the tourism sector are the highest contributors to Badung Regency's PAD. Keyword : PAD Badung Regency, COVID-19, Tourism, Economy Klasifikasi JEL : G51, I25, D31, E24